Stretch‐Safe: Magnetic Connectors for Modular Stretchable Electronics. (6th May 2020) - Kettlgruber, Gerald; Danninger, Doris; Moser, Richard; Drack, Michael; Siket, Christian M.; Wirthl, Daniela; Hartmann, Florian; Mao, Guoyong; Kaltenbrunner, Martin; Bauer, Siegfried
Abstract : Wearable healthcare devices monitor the condition of patients outside the hospital and hence increase treatment capacity and resources. At the same time, patients benefit from wireless data transmission and conformable device designs, speeding up the rehabilitation process and integration into normal daily activities. Yet, the successful implementation of personalized treatment creates an extensive engineering challenge as devices need to adapt to a vast number of different patients and treatment protocols. Herein, soft building blocks of mobile health (mHealth) devices that reversibly assemble through a magnetic click‐on mechanism are introduced. Fabrication of reliable magnetic connectors with an inherent safeguard mechanism allows the realization of personalized wearable mHealth devices, independent of the (desired) measurement technique. Stretchable elastomer‐based units combined with imperceptible electrodes are protected from overstretching by controlling the opening force of the magnetic connections. The stretchable devices retain both electrical and mechanical functionality for more than 10 000 opening cycles, on par with the standard for universal serial bus type C (USB C) connectors used in consumer electronics. A fully functional and autonomous pulse sensor wristband, assembled from the reliably connecting circuits, demonstrates the feasible implementation for mHealth devices. The plug‐and‐play modularity ensures the applicability independent of a patient's needs, without sacrificing functionality and durability. Abstract : Soft building blocks of mobile health devices that reversibly assemble through a magnetic click‐on mechanism are introduced, enabling personalized wearable medical monitoring equipment. Stretchable elastomeric units with imperceptible electrodes are protected from overstretching by controlling the opening force of the magnetic connections. High durability is evidenced with 10 000 opening cycles, empowering everyday applications such as an autonomous pulse sensor wristbands.